2020
DOI: 10.1515/hsz-2020-0184
|View full text |Cite
|
Sign up to set email alerts
|

ADAM8 affects glioblastoma progression by regulating osteopontin-mediated angiogenesis

Abstract: Glioblastoma multiforme (GBM) is the most aggressive type of brain cancer with a median survival of only 15 months. To complement standard treatments including surgery, radiation and chemotherapy, it is essential to understand the contribution of the GBM tumor microenvironment. Brain macrophages and microglia particularly contribute to tumor angiogenesis, a major hallmark of GBM. ADAM8, a metalloprotease-disintegrin strongly expressed in tumor cells and associated immune cells of GBMs, is related to angiogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…It plays an essential role in embryo development in the mouse ( Weintraub et al, 2004 ). Furthermore, osteopontin promotes invasion ( Ke et al, 2020 ) and angiogenesis in the trophoblast and other cells ( Li et al, 2021 ). Phosphatidylinositol 3-kinase (PI3K) is a heterodimer containing a regulatory subunit (p85) and a catalytic subunit (p110).…”
Section: Discussionmentioning
confidence: 99%
“…It plays an essential role in embryo development in the mouse ( Weintraub et al, 2004 ). Furthermore, osteopontin promotes invasion ( Ke et al, 2020 ) and angiogenesis in the trophoblast and other cells ( Li et al, 2021 ). Phosphatidylinositol 3-kinase (PI3K) is a heterodimer containing a regulatory subunit (p85) and a catalytic subunit (p110).…”
Section: Discussionmentioning
confidence: 99%
“…The angiogenic potential of ADAM8 in GBM cells and in primary macrophages is mediated by the regulation of osteopontin. ADAM8 could be a tractable target to modulate angiogenesis in GBM [ 74 ]. Zhu et al found that surgical debulking with anti-CD47 blocking immunotherapy causes a decrease in angiogenic proteins besides enhanced inflammatory response and prolonged survival in animals [ 75 ].…”
Section: Therapeutic Benefitsmentioning
confidence: 99%
“…Previous studies have shown that ADAM8 has significant roles in immunomodulation and inflammatory diseases [10][11][12]. ADAM8 is also associated with a variety of tumors, including glioblastoma and breast carcinoma, and is thus a promising potential therapeutic target [13,14]. In pancreatic ductal adenocarcinoma cells, functional inhibition of ADAM8 by BK-1361 was shown to lead to reduced invasiveness and less ERK1/2 and matrix metalloproteinase activation [15].…”
Section: Introductionmentioning
confidence: 99%